Telling Stories to Change the World - Richard Meyers (The University of Alabama, 2022)
Review of the book: Telling Stories to Change the World-Global Voices on the Power of Narrative to Build Community and Make Social Justice Claims. Edited by Rickie Solinger, Madeline Fox, and Kayhan Irani. (2008). New York: Routledge. ISBN: 0415960800 (paperback)